EFFECTS OF WEB-BASED METACOGNITIVE LISTENING ON CHINESE UNIVERSITY EFL LEARNERS' LISTENING COMPREHENSION AND METACOGNITIVE AWARENESS - Pei, Tao; Suwanthep, Jitpanat (Universitas Pendidikan Indonesia, 2019)
The present study examined the effects of web-based metacognitive listening practice on L2 learners? listening comprehension over 14 weeks. Participants (N = 67) came from two intact classes of intermediate EFL university learners in China. The experimental group was involved in the web-based metacognitive listening practice built on the metacognitive listening principles. The control group undertook a traditional web-based listening practice with the same listening materials texts, yet without training on their metacognitive awareness. TOEFL tests and MALQ were used to track the development of listening achievements and metacognitive awareness. ANCOVA was employed to detect the differences between the two groups regarding listening achievements and metacognitive development. The results show that the experimental group made significantly greater gains than the control group in listening achievements. However, the development of metacognition remained inconclusive. The study concludes that metacognitive listening practice under web-based environment could outperform the traditional web-based listening practice in improving listening achievements among Chinese intermediate EFL learners. Besides, some recommendations for further study are discussed.